LEGAL PROTECTION FOR HEALTHCARE WORKERSIN CRIMINAL MALPRACTICE CASES FROM THE PERSPECTIVE OF LAW NUMBER 17 OF 2023 ON HEALTH - Abdul Musyfiq Al Aytami; Dwi Andayani Budisetyowati; Noviriska (Adisam Publisher, 2026)
Providing quality healthcare is a state responsibility as mandated by Article 34(3) and Article 28H of the 1945 Constitution of Indonesia. However, malpractice issues in the healthcare sector remain a critical concern. This study aims to analyze the legal protection for medical and healthcare professionals accused of malpractice under Law Number 17 of 2023 on Health. It also examines the role of professional organizations in assisting their members in facing malpractice allegations in accordance with Article 440 of the law. Case studies on three legal matters highlight the importance of adherence to Standard Operating Procedures (SOPs) to protect patients from medical negligence. The findings reveal that although the law provides legal protection, its practical implementation often falls short. Therefore, public education, enhanced oversight, and regulatory improvements are necessary. Legal protection is not only intended to safeguard healthcare professionals but also to ensure justice and legal certainty for all parties involved.